Cu(acac)2-Catalyzed A3-(Aldehyde-amine-alkyne) Coupling Reaction for the Synthesis of a Wide Range of Propargylamines and Entry to Imidazo[1,2-a]pyridines - Pappula, Upendra; Kalyana, Venkata Prasad; Roy, Ujjal Kanti (Synthesis, 2025)
Cu(acac)2-catalyzed A3-coupling reactions involving an amine, an aldehyde, and a terminal alkyne were explored for the efficient synthesis of a broad range of propargylamines and imidazo[1,2-a]pyridines. This method demonstrates a wide substrate scope and delivers the desired products in good yields under mild reaction conditions. The protocol offers a straightforward and practical approach to accessing these valuable scaffolds, making it attractive for further synthetic applications.
Keywords: Copper catalyst; A3-Coupling; Propargylamines; Imidazo[1,2-a]pyridine